2009
DOI: 10.4049/jimmunol.0802531
|View full text |Cite
|
Sign up to set email alerts
|

Absence of Mucosal Immunity in the Human Upper Respiratory Tract to the Commensal Bacteria Neisseria lactamica but Not Pathogenic Neisseria meningitidis during the Peak Age of Nasopharyngeal Carriage

Abstract: The normal flora that colonizes the mucosal epithelia has evolved diverse strategies to evade, modulate, or suppress the immune system and avoid clearance. Neisseria lactamica and Neisseria meningitidis are closely related obligate inhabitants of the human upper respiratory tract. N. lactamica is a commensal but N. meningitidis is an opportunistic pathogen that occasionally causes invasive disease such as meningitis and septicemia. We demonstrate that unlike N. meningitidis, N. lactamica does not prime the dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
44
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(45 citation statements)
references
References 63 publications
(89 reference statements)
1
44
0
Order By: Relevance
“…Carriage of N. meningitidis is also associated with mucosal regulatory T cell activity, which may prevent immunopathology and promote continued carriage (8). Conversely, although carriage of N. lactamica has been associated with increased titers of antimeningococcal Ig in the periphery during the peak period of nasopharyngeal carriage (17), N. lactamica appears to evade the adaptive immune system in the URT mucosa, failing to prime the development of immunological memory (9). T cell responses only become detectable to N. lactamica Ags in older individuals, presumably as a result of cross-reactivity with N. meningitidis proteins or to other commensal Neisseria species to which they develop memory following carriage (9).…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…Carriage of N. meningitidis is also associated with mucosal regulatory T cell activity, which may prevent immunopathology and promote continued carriage (8). Conversely, although carriage of N. lactamica has been associated with increased titers of antimeningococcal Ig in the periphery during the peak period of nasopharyngeal carriage (17), N. lactamica appears to evade the adaptive immune system in the URT mucosa, failing to prime the development of immunological memory (9). T cell responses only become detectable to N. lactamica Ags in older individuals, presumably as a result of cross-reactivity with N. meningitidis proteins or to other commensal Neisseria species to which they develop memory following carriage (9).…”
mentioning
confidence: 99%
“…Conversely, although carriage of N. lactamica has been associated with increased titers of antimeningococcal Ig in the periphery during the peak period of nasopharyngeal carriage (17), N. lactamica appears to evade the adaptive immune system in the URT mucosa, failing to prime the development of immunological memory (9). T cell responses only become detectable to N. lactamica Ags in older individuals, presumably as a result of cross-reactivity with N. meningitidis proteins or to other commensal Neisseria species to which they develop memory following carriage (9). Although N. lactamica evades priming immunological memory, we have also shown that outer membrane vesicles (OMVs) prepared from this bacteria stimulate a potent proliferative response in tonsillar mononuclear cell (TMNC) cultures from young children and adults that is absent in response to N. meningitidis.…”
mentioning
confidence: 99%
See 3 more Smart Citations